Effects of a combined stretching training on flexibility of students in sports science program Silpakorn University - Boonsom, Niwat (Universitas Nusantara PGRI Kediri, 2020)
The research aimed to compare the effect of combined stretching training on flexibility and to compare the difference of the flexibility between male and female students in sports science program after 8 week of training. The subjects were 20 (10 male, 10 female) of the first year students in sports science program, Silpakorn University. The trainings were done in 30 minutes per day, 3 days per week, for 8 weeks. The flexibility tests were done every 2 weeks of training until 8 week. The data were analyzed by mean, standard deviation, One-way Analysis of Variance with repeated measures and compared in pair by using Bonferroni method with statistically significant at .05. The results showed the flexibility of male and female students in sports science program after the combined stretching training program was different with statistically significant at .05 and the difference in the flexibility of female students after 8 week of the combined stretching training program were increased higher than male students. In summary, the combined stretching training program can increase the flexibility both of the male and female students in sports science program and can increase flexibility in female more than male students. This study is limited from subjects improperly cloth. Certain sportswear does not allow the flexibility of the fabric during exercise. Further study should study the effects of combined stretching training program on the performance measures.